The development of Malaysian Corpus of Financial English (MaCFE) - Roslan Sadjirin; Roslina Abdul Aziz; Noli Maishara Nordin; Mohd Rozaidi Ismail; Norzie Diana Baharum (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper presents the processes involved in the design and development of the Malaysian Corpus of Financial English (MaCFE); a specialized corpus containing a wide range of online/internet documents (i.e. communiqué) from various financial institutions in Malaysia. It describes in detail the processes involved in the collection and selection of data and preprocessing of raw data, which includes data digitizing, cleansing and tagging. This paper also introduces the user interface for MaCFE with its built-in linguistic analysis features. MaCFE was designed and developed with the intention of providing corpus linguistic researchers with the avenue to explore the field and for ESP/EAP practitioners in Malaysia, as the resources for the development of local-based ESP/EAP curriculum and teaching and learning materials. It would also serve as a learning avenue for future financial professionals in their training. MaCFE corpus has approximately 4.3 million words from 1472 electronic documents retrieved from banks and financial institutions’ official websites. At present, users can make queries to the MaCFE database using its built-in concordancer. In the future, its language-data-processing facilities will be expanded to include tools for keyword, wordlist and word collocations queries.